Peran Guru PAI Dalam Membangun Moderasi Beragama di SDIT Baitul Jannah Bandar Lampung: Peran Guru PAI Dalam Membangun Moderasi Beragama di SDIT Baitul Jannah Bandar Lampung - Munawaroh; Fairuz Fathin F (Program Studi Pendidikan Agama Islam, 2023)
Religious moderation accepts differences, is open and maintains harmony between religious communities. Strengthening moderation needs to be introduced from an early age to students to avoid radical thinking and closing off others through the role of a religious teacher. The aim is to describe the role of PAI teachers and determine the supporting and inhibiting factors in building religious moderation. Method with a descriptive qualitative approach. The research location is SDIT Baitul Jannah Bandar Lampung. Data collection using interview and documentation techniques. Data analysis by collecting data, reducing data, presenting and drawing conclusions. The results show that: 1. The role of PAI teachers in building religious moderation at SDIT Baitul Jannah Bandar Lampung includes: a. Conservator as PAI teacher is responsible for his/her attitude, b. PAI teacher transmitter (successor) as motivator and guide, c. PAI teacher innovator (developer) collaborates with other teachers, d. Organizer (implementer) of innovation activities, e. Transformer, PAI teacher becomes an example for students; 2. The values ​​of religious moderation that are built include; justice (adl), balance (tawazun), simplicity (I'tidal), unity and brotherhood (ittihad wa ukuwah). 3. Supporting factors, namely the PAI teacher himself, has the personal capacity and experience that supports building religious moderation. Then facilities such as mosques, ablution places, worship practice programs. As for inhibiting factors, there are no significant inhibiting factors, only the need for cooperation and consistency among school residents and student guardians to understand the importance of religious moderation.